PENINGKATAN PROSES DAN HASIL BELAJAR GEOGRAFI MELALUI OPTIMALISASI LINGKUNGAN SEBAGAI SUMBER BELAJAR DENGAN PENDEKATAN SCIENTIFIC PADA MATERI INTERAKSI MANUSIA DAN LINGKUNGAN DALAM DINAMIKA ATMOSFER TAHUN AJARAN 2013/2014 - astuti, tanjung fitri (Pendidikan Geografi, 2013)
PENINGKATAN PROSES DAN HASIL BELAJAR GEOGRAFIMELALUI OPTIMALISASI LINGKUNGAN SEBAGAI SUMBER BELAJAR DENGAN PENDEKATAN SCIENTIFIC PADA MATERI INTERAKSI MANUSIA DAN LINGKUNGAN DALAM DINAMIKA ATMOSFERTAHUN AJARAN 2013/2014Tanjung Fitri Astuti1,*Danang Endarto, S.T, M.Si 2Singgih Prihadi, S.Pd, M.Pd 2 1 Mahasiswa S1 Pendidikan Geografi FKIP Universitas Sebelas Maret Surakarta2Dosen Pendidikan Geografi FKIP Universitas Sebelas Maret Surakarta*Keperluan korespondensi, HP : 085642065211, e-mail : tanjung393@gmail.com ABSTRACTThe purpose of this study were 1) to determine the environment optimalization as a learning resource of the scientific approach in improving the process of students of learning geography on the material about human and environment interactions in dynamical atmosphere in SMA N 1 Karanganyar. 2) to optimize the environment as a learning resource through the scientific approach in improving the learning outcomes of students in the geography material of human interaction and the environment in the dynamical atmosphere in SMA N 1 Karanganyar.This research is Classroom Action Research carried out in two cycles. The subjects of the study were the students of class X Science 2 SMA N 1 Karanganyar in the Academic Year 2013/2014, there are 35 students. The object of the research is the process and outcomes of learning geography on the material of human and environment interaction in dynamical atmosphere that is related to the optimization of learning environment. The data were obtained through observation, interviews, tests, questionnaires and documentation. The data analysis technique used was a critical and comparative descriptive analysis. The validity of the data used triangulation technique.The results showed that the application of the optimization of the environment as a learning resource to the scientific approach to the material of human and environment interactions in dynamical atmosphere can improve the process and outcomes of learning Geography. This can be seen in the implementation of the first cycle and second cycle. In the first cycle, the indicator of students learning mastery was 65.7% and it increased to 85.7% in the second cycle. Then the indicator of students learning process in the first cycle was 74.7% and it increased to 87.7% in the second cycle, the indicator liveliness and motivation of students in the first cycle of 66.9% increased to 80.4% in the second cycle. Keywords: Process and Learning Outcomes, Learning Resources Environment, Scientific Approach